Comparison of a finite volume and two Lattice Boltzmann solvers for swirled confined flows - Aniello, A.; Schuster, D.; Werner, P.; Boussuge, J. F.; Gatti, M.; Mirat, C.; Selle, L.; Schuller, T.; Poinsot, T.; Rüde, U. (Computers & Fluids, 2022)
A finite volume and two Lattice–Boltzmann unsteady, flow solvers using LES (Large Eddy Simulation) were compared in a swirling flow configuration, typical of aeronautical combustion chambers. Numerical results were validated against experimental data collected at EM2C laboratory by comparing pressure losses, mean and RMS velocity profiles on multiple planes and axial velocity spectra. Meshes and the overall numerical setups were individually adjusted for each code to obtain the targeted accuracy before comparing CPU efficiencies. Results confirm that the three LES codes provide high fidelity results, much better than usual RANS especially in terms of RMS data. The analysis of CPU performances shows that LBM (Lattice–Boltzmann Method) solvers are faster than the finite volume solver, even if CPU efficiencies remains of the same order of magnitude. In addition, strong scaling tests from 36 to 900 cores show that the finite volume solver scales more efficiently than the LBM codes, specially when the number of grid points per core is not sufficient.
CRIS-Team Scopus Importer:2022-05-20
Keywords: CPU efficiency; Large Eddy Simulation; LBM and FVM comparison; Swirling flow